Teach yourself visually more jewelry making - Michaels, Chris Franchetti
Unlike other crafts that focus on a fairly narrow range of techniques and materials, jewelry making is very broad; the techniques encompass everything from bead stringing to metal stamping to working with different types of clay. More Teach Yourself VISUALLY Jewelry Making picks up where Teach Yourself VISUALLY Jewelry Making & Beading leaves off and gives you even more techniques to create new types of jewelry